Повышение эффективности силового размещения компонентов - Dmitriev, P. I.; Zudin, S. V.; Luzin, M. S.; Polubasov, O. B. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A method is proposed to improve the efficiency of power-optimized component placement, which includes: calculating the optimal component placement that is close to the placement ensuring the minimum total connection length; discretization of the solution, taking into account the dimensions and orientation of the components, as well as the number of contacts involved; construction (reconstruction) of the shortest spanning trees for each of the circuits.